ANALISIS PENERAPAN ISO 45001 : 2018 DI PT KERETA API INDONESIA (PERSERO) UPT BALAI YASA MANGGARAI TAHUN 2023 - Nabila Izzani (2024)
Balai Yasa Manggarai is a train repair and maintenance workshop under PT Kereta Api Indonesia (Persero), will renew the ISO 45001:2018 KAN standard certification. Based on the results of both internal and external audits, some changes require adjustment and development stages that need to be improved in adapting to the ISO 45001:2018 standard. This research aims to analyze the implementation of ISO 45001:2018 to prevent work accidents at Balai Yasa Manggarai in 2023. The method used in this research is descriptive qualitative, data collection uses a purposive sampling technique for 4 informants, such as the K3 team leader, the head of the program ISO 45001:2018, K3 team members for administration, and K3 team members. The instruments of this research were a field observation checklist and a review of company documents, and in-depth interviews were also conducted based on ISO 45001:2018 guidelines. Data validation uses source triangulation and method triangulation. The results of the research show that Balai Yasa Manggarai achieved a score of 92.64% in compliance with the guidelines, meaning that the value measurement index was declared very good. With a note of inconsistency in clauses 8.1; 9.2; 9.3; and 10. So, a strategy is carried out to maintain and improve the company in preparation for the next ISO 45001:2018 certification assessment.